Renhed og urenhed i singhalesisk folkereligion - Andersen, Grethe Schmidt (Religionsvidenskabeligt Tidsskrift, 1997)
The article introduces notions of ritual impurity in Sinhalese culture and examines why conditions of impurity specially influence certain lower local gods and demons. The Sinhalese pantheon is based on a principle of hierarchy, with an opposition of high and low that corresponds to notions of purity and impurity determined by the ultimate Buddhist goal - the attainment of Nirvana. Two ritually important concepts of impurity and pollution are introduced: pilikul and killa, which are connected with special items of food and phases (menstruation, birth and death). These concepts of impurity have importance in the ritual meeting between man, gods and demons, but they are not corresponding to the moral concepts of purity in the pantheon, and it seems that the lower gods are more influenced by impurity than the higher gods. Impurity is connected with the exchange between nature and culture and articulates the danger of potential disorder between the two areas. The local gods, who are responsible for fertility, are situated in a vulnerable but dynamic position in the panthon, where the exchange between high and low, pure and impure takes place, and where divine power may change into the demonic and vice versa. The local gods are both dangerous and necessary: dangerous because they represent potential disorder and necessary because they are the dynamics of the exchange. The ritual handling of impurity articulates the borderline of purity/fertility and impurity/fertility and maintains dynamics of transformation and order.